Decontamination of a Feed Manufacturing Environment Following Inoculation with Porcine Epidemic Diarrhea Virus, Porcine Reproductive and Respiratory Syndrome Virus, and Seneca Valley Virus 1 - Olivia L. Harrison; Haley K. Otott; Jianfa Bai; Vaughn A. Hamill; Aaron Singrey; Phillip C. Gauger; Marcelo N. Almeida; Jason C. Woodworth; Charles R. Stark; Roman M. Pogranichniy; Cassandra K. Jones; Jordan T. Gebhardt; et al. (Kansas Agricultural Experiment Station Research Reports, 2024)
Feed mill decontamination is difficult because equipment is not designed to be cleaned with water. Alternate strategies may improve a mill’s ability to decontaminate in the event of viral contamination. The objective of this experiment was to evaluate different decontamination strategies within a mill following the inoculation of swine feed with porcine epidemic diarrhea virus (PEDV), porcine reproductive and respiratory syndrome virus (PRRSV), and Seneca Valley virus 1 (SVV1) run through feed manufacturing equipment consisting of a mixer, bucket elevator, corn cleaner, drag conveyor, and distributor. Afterward, decontamination strategies were implemented with environmental samples collected after each step. Strategy treatments included: 1) complete facility decontamination and heating for 48 hours at 60°C; 2) chlorine dioxide application (ProOxine AH, Bio-Cide International, Inc., Norman, OK); 3) organic matter removal using vacuums (Ridge Tool Company, Elyria, OH) and chlorine dioxide application; 4) heat with portable electric heaters for exactly 48 hours; and 5) organic matter removal and heat with portable heaters for exactly 48 h. A swine bioassay was completed to determine the infectivity of each treatment after decontamination. A treatment × decontamination step × location interaction was observed (P < 0.05) for SVV1, where less RNA was detected post-treatment compared to post-inoculation following the complete facility decontamination treatment on surfaces including the mixer, corn cleaner, drag conveyor, and flooring (P < 0.05) as compared to all other decontamination treatments. Across all treatments, the act of decontamination reduced detectable PEDV (P < 0.05) and PRRSV (P < 0.05) RNA when compared to samples immediately following inoculation, but complete facility decontamination and heating was the only treatment RNA was non-detectable in all locations. Pigs inoculated with samples collected post-treatment showed no evidence of SVV1 or PEDV infection; PRRSV infection was observed in pigs given the chlorine dioxide with and without organic matter removal treatments and the organic matter removal plus heat treatment. Overall, all treatments reduced detectable RNA for all viruses between the inoculation step and the final decontamination step; however, PRRSV particles remained infectious following decontamination.
Keywords: chlorine dioxide; decontamination; feed mill; heat; viruses